Exploring agile mobile app development in industrial contexts: a qualitative study - Asfour, Ali; Zain, Samer M.; Salleh, Norsaremah; Grundy, John (International Journal of Technology in Education and Science (IJTES), 2019)
Agile development methods have been proposed as a natural fit for mobile app development contexts. Despite many studies addressing the adoption of agile methods for traditional web and desktop applications, there is a lack of studies of how mobile app development teams can adopt agile methods and the challenges they are facing. Our study explores this area to better understand how some representative industrial teams approach agile mobile app development, and the challenges they are facing. We conducted a qualitative study involving four different mobile app development companies. Our research method is based on multiple-case study design. From our findings, we argue that not all agile development principals are necessarily applicable within the mobile app development context. Furthermore, mobile app development teams face additional challenges when adopting agile methods such as development automation tools and on-line app store restrictions to mention a few. To our best knowledge, this is the first study that explores industrial teams from the perspective of agile development. Our results provide in-depth guidance to practitioners and highlights areas of research that require further investigation.